PERAN KUALITAS AUDIT MEMODERASI PENGARUH AFILIASI KELOMPOK BISNIS TERHADAP MANAJEMEN LABA - Pratiwi Indah Kurniati; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
The aim of this study is to examine the moderating role of audit quality in the influence of business group affiliation to earnings management. Audit quality was measured by two proxies, there are audit firm Big4 and industry specialisation auditor. Earnings management was measured using the value of discretionary accruals. Beside that, this study used size of a firm as control variables. A usable sample of this study was manufacture and service firms which listed on Indonesian Stock Exchange for the period 2016. The number of sample are 107 samples. Research data were obtained from the annual reports of sample firms. The used sampling method is purposive sampling method. Hypothesis testing is done with Ordinary Least Square (OLS) analysis. The results of the research show that business group affiliation influence negatively to earnings management, and then audit quality weaken that influence.